Use of a focus group-based cognitive interview methodology to validate a cooking behavior survey among African-American adults - Farmer, Nicole; Powell-Wiley, Tiffany M.; Middleton, Kimberly R.; Brooks, Alyssa T.; Mitchell, Valerie; Troncoso, Melissa; Ceasar, Joniqua; Claudel, Sophie E.; Andrews, Marcus R.; Kazmi, Narjis; Johnson, Allan; Wallen, Gwenyth R. (Frontiers in Nutrition, 2022)
Disparities in diet-related diseases persist among African-Americans despite advances in risk factor identification and evidence-based management strategies. Cooking is a dietary behavior linked to improved dietary quality and cardiometabolic health outcomes. However, epidemiologic studies suggest that African-American adults report a lower frequency of cooking at home when compared to other racial groups, despite reporting on average time spent cooking. To better understand cooking behavior among African-Americans and reported disparities in behavior, we sought to develop a survey instrument using focus group-based cognitive interviews, a pre-testing method that provides insights into a survey respondent’s interpretation and mental processing of survey questions. A comprised survey instrument was developed based on input from a community advisory board, a review of the literature, and a content review by cooking behavior experts. Cognitive interview pre-testing of the instrument involved African-American adults (n=11) at risk for cardiovascular disease who were recruited from a community-based participatory research study in Washington, D.C. to participate in a focus group-based cognitive interview. Cognitive interview methodologies included the verbal think-aloud protocol and the use of retrospective probes. Thematic analysis and evaluation of verbalized cognitive processes were conducted, using verbatim transcripts. Five thematic themes related to the survey were generated: 1) Clarity and relevancy of question items; 2) Influence of Participant’s Perspectives and Gender Roles; 3) Participant Social Desirability Response to Questions; 4) Concern Regarding Question Intent. Eleven survey items were determined as difficult by participants. Cooking topics for these items were: cooking practices, cooking skills, cooking perception (how one defines cooking), food shopping skills, and socialization around cooking. Question comprehension and interpreting response selections were the most common problems identified. Cognitive interviews are useful for cooking research as they can evaluate survey questions to determine if the meaning of the question as intended by the researcher is communicated to the respondents. Specific implications from the results that apply to cooking research included revising questions on cooking practice and skills. Focus-group based cognitive interviews may provide a feasible method to develop culturally grounded survey instruments to help understand disparities in behavior for culturally-relevant diet behaviors, such as cooking.